2008
DOI: 10.1007/s00431-008-0885-9
|View full text |Cite
|
Sign up to set email alerts
|

Extrauterine growth retardation in premature infants in Shanghai: a multicenter retrospective review

Abstract: Intrauterine growth retardation (IUGR) represents the degree of body growth and development decided by genes and by placental function. Extrauterine growth retardation/restriction (EUGR) refers to severe nutritional deficits during the first weeks of life that result in growth that is less than expected based on intrauterine growth rates (growth values < or =10th percentile of intrauterine growth expected in accordance with the estimated gestational age). The deficits affect not only weight but also head circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 15 publications
6
32
1
Order By: Relevance
“…In other words, the chance of reaching a normal weight decreases as the time to achieve a normal growth rate increases 2,41,42,[45][46][47] . On the other hand, Shan et al 32 associated EUGR with an increase in gestational age, which agrees with our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In other words, the chance of reaching a normal weight decreases as the time to achieve a normal growth rate increases 2,41,42,[45][46][47] . On the other hand, Shan et al 32 associated EUGR with an increase in gestational age, which agrees with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Gianini et al 28 also associated small for gestational age at birth with EUGR. Other studies have also found this association, but the EUGR rates varied from 16.0 to 63.0% [29][30][31][32] . Shan et al 32 found EUGR in 44.0% to 62.2% of premature infants.…”
Section: Discussionmentioning
confidence: 67%
“…6,14,44,45 In our population, the frequency of newborns with weight below the 10 th percentile for age increased from 30.4% at birth to 76.1% at post-conceptual age of term, and the associated factors were SGA, sepsis and higher time for attaining exclusive enteral nutrition. The association between restriction of extra-uterine growth, SGA, bronchopulmonary dysplasia, number of days of parenteral nutrition and age to attain exclusive enteral nutrition has also been shown in other studies.…”
mentioning
confidence: 78%
“…In Senegal, Faye et al [32] reported extra-uterine growth retardation (86%), underweight (61%), and underweight at 40 weeks post-conception (41%), at 3 months and at 6 months of gestation-adjusted age. Other higher rates of underweight were reported in Morocco (77.5%) [33], Tunisia (55%) [34], China (56.8%) [35] and Japan (49%) [36].…”
Section: Discussionmentioning
confidence: 95%